Analysis of Quiz as programmatic strategy of Neo Television in Spain - Gallego Trijueque, Sara; Oliva Marañón, Carlos; Cejudo Mejías, Vanesa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
It is in the US where television quiz originate, being inspired by those that were already carried out on the radio. The objective is to analyse the entertainment programs of Antena 3, Tele 5, Cuatro, and La Sexta in the 2010-2020 decade. The broadcast time of the contest (morning, afternoon, Prime Time), the format (quiz show, game show, and talent), the timing, the gender of the presenter, and his role have been studied. The results confirm the homogeneity in the broadcast periods, the variety of formats, the prevalence of the male gender in the presenters, and the pre-eminence of British quiz.